Simplified Modeling of Wind-driven Single-sided Ventilation - Albuquerque, D.P. (2021)
In the last decades there has been an expansion in the use of building mechanical cooling systems. This increase is due to several factors such as global warming, higher internal heat gains, widespread use of unshaded glazed façades and more stringent thermal comfort requirements. In mild to warm climates, buildings without operable windows require mechanical cooling during most of the year, even in moments when the outdoor conditions would allow for natural cooling by ventilation. To reverse this trend designers are encouraged to use natural cooling strategies such as natural ventilation (NV). A well-designed building NV system can reduce building energy use and contain the increasing demand for mechanical cooling systems in buildings. Unfortunately, building designers often struggle when trying to predict the performance of an NV system due, in part, to the lack of precision of the existing simple models for NV airflow in real-world conditions. This thesis investigates the wind driven NV airflow over a multitude of NV systems: night ventilation (NVC), single sided ventilation (SS1), pumping ventilation (SS2 and CR2), and corner ventilation (CR2). For these NV systems, this thesis developed simplified correlations that improve existing models for predicting these NV airflows. The results of this research show that NV systems can be modeled using simple correlations that can assist designers in the integration of these systems in modern buildings. The experimental study of NVC showed that this strategy can significantly reduce mechanical cooling load. The study of window effects on wind driven NV in SS1 systems showed that the window geometry can significantly increase the ventilation flow. Finally, the studies on pumping ventilation showed that this recently discovered ventilation mechanism is very prevalent in isolated buildings with SS rooms with two or more openings.